Health Education about the Benefits of Covid-19 Vaccination in the community in Pegadingan Village, the working area of the Kramatwatu Health Center, Serang, Banten - Deni Suwardiman; Agus Sustiyono (Jurma : Jurnal Program Mahasiswa Kreatif, 2022)
The global condition of the Covid-19 pandemic brings a valuable message to the Indonesian people, especially the people of Banten. The rapid transmission in a short time drains the government's energy and thoughts, especially in the health sector to cope with the Covid-19 pandemic. Efforts to limit community activities, implementation of health protocols, and Covid-19 vaccination are the government's flagship programs for the community. On the other hand, the development of hoax news also worsens the condition of people's knowledge and attitudes in dealing with the Covid-19 pandemic. To support the implementation of the Covid-19 vaccination program, the Universitas Faletehan academic community is moving in synergy with the Serang District Health Office through collaboration with the Kramatwatu District and the Kramatwatu Health Center to carry out Health Education and administering the Covid-19 vaccine, one of which is in Kampung Gempol, Desa Pegadingan, Kramatwatu Serang, Banten with a target of 100 people, the target was 87 people, preceded by the provision of Health Education about the benefits of the Covid-19 vaccine in the hope that the public will gain knowledge and can influence other communities regarding the importance of the Covid-19 vaccine. Based on the indicators of knowledge measurement before and after Health Education was carried out, it was found that there was a difference in the average value before and after the achievement of changes in the maximum and minimum values, so it can be stated that the implementation of Health Education was very effective given to the community. So it is recommended to the Department of Health and related parties carry out this Health Education in a planned and scheduled manner for the wider community.